Study on Heat Transfer Enhancement of Lotus-type Porous Copper Heat Sink - Wu Jian; Liu Yuan; Li Yanxiang; Zhang Huawei (Zhileng xuebao)
Lotus-type porous copper is a new kind of micro-channel structure with long cylindrical pores aligned in one direction. It can be used as a heat sink for cooling of high-power electronic components. Through experiments and numerical simulations with Flow Simulation, the heat transfer performance of a lotus-type porous copper heat sink with uniform distributed micro-groove was systematically studied. The experimental results showed that this kind of heat sink has an excellent heat transfer coefficient, as high as 10.1 W/(cm2?K), only under a flow rate as low as 110 mL/s. The simulation showed that optimal number and angle of micro-groove existed for the heat sink to reach a maximal equivalent heat transfer coefficient. For water as its coolant, the optimal number and angle of micro-groove were 7-11 and 45°, respectively. And heat transfer performance of the heat sink continuously improved with decreasing of the width of micro-groove. The numerical simulation results were compared with the experimental results, and the reasons for the differences were analyzed.